2016
DOI: 10.1186/s40659-016-0097-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone in the presence of laminin modulates interaction of human thymic epithelial cells and thymocytes in vitro

Abstract: Background: Several evidences indicate that hormones and neuropeptides function as immunomodulators. Among these, growth hormone (GH) is known to act on the thymic microenvironment, supporting its role in thymocyte differentiation. The aim of this study was to evaluate the effect of GH on human thymocytes and thymic epithelial cells (TEC) in the presence of laminin.Results: GH increased thymocyte adhesion on BSA-coated and further on laminin-coated surfaces. The number of migrating cells in laminin-coated memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…In total, 69 articles were found that refer to these cell lines, in turn cited by 2092 articles. Of the primary articles, 43 were published after the report by MacLeod et al and the most recent one was published only in late 2016 [41]. Of the fifteen most recent articles referring to the 1994 report, thirteen actually refer to it because they use the cell lines, all thirteen reporting research on thymic cells, without mentioning any knowledge of the misidentification of these cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 69 articles were found that refer to these cell lines, in turn cited by 2092 articles. Of the primary articles, 43 were published after the report by MacLeod et al and the most recent one was published only in late 2016 [41]. Of the fifteen most recent articles referring to the 1994 report, thirteen actually refer to it because they use the cell lines, all thirteen reporting research on thymic cells, without mentioning any knowledge of the misidentification of these cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Most likely, at least part of the GH effects upon the thymus is related to the modulation of cell adhesion and migration. Accordingly, in vitro treatment of murine and human TECs with GH resulted in increased deposition of fibronectin and laminin and their respective receptors, VLA-5, and VLA-6 ( 114 , 115 ). Also, thymocyte adhesion to GH-treated TECs is upregulated, and exposure of these cells to anti-GH antibodies or anti-ECM abolished the effect ( 116 ).…”
Section: Pleiotropic Effects Of Gh Igf-1 Ghrelin and Somatostatin Upo...mentioning
confidence: 99%
“…СТГ регулирует тимическое микроокружение, повышая секрецию и высвобождение цитокинов (прежде всего интерлейкина-1 и интерлейкина-6 [37]), хемокинов и тимулина [7,35,38,39,43,46], модулируя при этом адгезию и миграцию тимоцитов [32,36,37], а также выработку белков внеклеточного матрикса [36]; увеличивает отложение (депонирование) белков, способствующих миграции клеток, таких как ламинины и стромальный клеточный фактор-1 [44]. В эксперименте миграция тимоцитов, полученных от трансгенной по ГР мыши или от мыши, в тимус которой был инъецирован этот гормон, усиливается в сторону источников стромального клеточного фактора-1 и ламининов [44].…”
Section: тимус и гормоны соматотропной осиunclassified